(untitled) (International Journal of Applied Research in Management and Economics, 2020)
The Ricardian Equivalence Hypothesis formulated by a classical British economist David Ricardo argues that a reduced tax now is a tax increase in the future, the substitution of debt for current taxes has no effect on aggregate demand. The main objective of this paper is to examine empirically the existence of the Ricardian equivalency in Ghana by using time series data running from 1990 to 2017 and ARDL bound testing approach to cointegration and Error Correction Model framework developed by Pesaran and Shin (1995,1999). We examined the long run relationship between the dependent variable household final consumption expenditure and independent variables government expenditure, deficit, GDP per capita and gross debt. The long run results showed a positive and significant relationship between GDP per capita and household consumption expenditure. The result of analysis supports the Keynesian conventional theory and found strong evidence against the existence of the Ricardian Equivalency Hypothesis in Ghana.